An Experimental Study Of Oscillating Subboundary Layer Vortex Generators Application On A Wing'S Flap - Hussin, Fauzi (2014)
Flow control to suppress the boundary layer separation over the wmg can dramatically improve the performance of most aircraft in the take-off and lancling flight regime. Previous aerodynamic experiments and computations have indicated that unsteady excitation produced by the oscillating sub boundary layer vortex generators (SBVGs) can delay boundary layer separation and wing stall more effectively than steady flow perturbations generated by passive SBVGs. Preliminary aerodynamic experiments have been performed to evaluate the effects of both passive and oscillating SBVGs on the wing of Eagle 150B with a single slotted flap at deflection angle of 38°. Four sets of co rotating, delta shaped vane type SBVGs have been installed near to the leading edge of the flap. In addition, oscillating SBVGs were designed to oscillate in three different frequencies (0.5Hz, 1.2Hz and I. 7Hz). Baseline (No VGs), passive and oscillating SBVGs were tested at three different Reynolds numbers (Re=6.21 x lOS, Re=7.3xIOs and Re=8.4xIOs) and the aerodynamic characteristics were obtained using six-component balance instrument. For the baseline case (No VGs), its lift and drag characteristic at Reynolds number of 8.4x lOS and angle of attack of 26° varies with the theoretical data by 50% and 26.38%, respectively.